2003
DOI: 10.2337/diacare.26.7.2139
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Blood Interleukin-6 Levels in Hyperketonemic Type 1 Diabetic Patients and Secretion by Acetoacetate-Treated Cultured U937 Monocytes

Abstract: OBJECTIVE -Diabetic patients have elevated blood levels of interleukin-6 (IL-6), which is known to increase inflammation and the development of vascular disease and atherosclerosis. This study examined the hypothesis that ketosis increases the circulating levels of IL-6 in type 1 diabetic patients as well as the secretion of IL-6 in vitro in a cell culture model using U937 monocytes.RESEARCH DESIGN AND METHODS -Fasting blood was obtained from type 1 diabetic patients and healthy siblings. To examine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 35 publications
(35 reference statements)
4
75
0
4
Order By: Relevance
“…However, AA differs from 3HB in that it also has unique functions in various biological processes, such as insulin release in vitro, generation of free oxygen radicals, lipid peroxidation, and activation of the ERK1/2 and p38 MAPK signaling pathways (45,46,49). In this report, we demonstrate for the first time that AA-mediated promotion of muscle cell proliferation is not a generalized ketone body effect but instead is specific to AA.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, AA differs from 3HB in that it also has unique functions in various biological processes, such as insulin release in vitro, generation of free oxygen radicals, lipid peroxidation, and activation of the ERK1/2 and p38 MAPK signaling pathways (45,46,49). In this report, we demonstrate for the first time that AA-mediated promotion of muscle cell proliferation is not a generalized ketone body effect but instead is specific to AA.…”
Section: Discussionmentioning
confidence: 65%
“…AA also stimulates chaperone-mediated autophagy (47) and down-regulates the expression of ATP-binding cassette transporter A1 (ABCA1) in vitro (48). AA, but not 3HB, promotes the secretion of interleukin (IL)-6 in cultured U937 monocytic cells (49). Interestingly, in neural cells, AA exerts its protective effect against glutamate-induced oxidative stress on HT22 cells and rat primary hippocampal neurons by decreasing glutamate-induced production of reactive oxygen species (50).…”
mentioning
confidence: 99%
“…Furthermore, BBR supplementation in rats increased the expression of sirtuin 1 (SIRT1), a deacetylase with antioxidant activity (Gomes et al, 2012). In conjunction with oxidative stress, pro-inflammatory cytokines are elevated in the blood of both diabetic animals and human patients (Jain et al, 2003;Mahmoud et al, 2012). Increased pro-inflammatory cytokines including IL-6 lead to reduction in IRS-1 tyrosine phosphorylation and association with phosphatidylinositol (PI)-3 kinase, inhibition of Akt activation (Bastard et al, 2000;Senn et al, 2002) and suppressed lipoprotein lipase (LPL) activity (Greenberg et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that hyperglycaemia increases serum concentrations of IL-6 [11,12] possibly through augmented production in monocytes [11,13]. Thus patients with diabetes have elevated blood levels of IL-6, which, together with TNF-α are known to increase inflammation and the development of vascular disease and atherosclerosis, possibly by increasing oxidative stress [12,14,15,16]. In children with T1DM, IL-6 levels were found to be statistically significantly increased in the group with long T1DM duration, as well as in those newly diagnosed, when compared with healthy controls [6,9], with the highest levels in the newly diagnosed patients [9].…”
Section: Methodsmentioning
confidence: 99%
“…Although there are some previous studies on the role of cytokines in the development of long-term diabetes complications [6,9,12,14,15,16], there is only one study on the fluctuation of cytokines during the metabolic crisis of DKA in children with T1DM [6], including limited number of patients. The aim of the present study was to monitor serum levels of pro-inflammatory cytokines IL-1β, IL-2, IL-6, IL-8 and TNF-α and the anti-inflammatory cytokine IL-10 at different time-points during the management of DKA, as markers of the risk of development of its acute complications.…”
mentioning
confidence: 99%